MTA-induced neutrophil recruitment: a mechanism dependent on IL-1β, MIP-2, and LTB4 - Gomes, Alessandra Cristina [UNESP]; Gomes Filho, João Eduardo [UNESP]; Oliveira, Sandra Helena Penha de [UNESP] (Elsevier, 2008)
Objective: The objective of this study was to investigate the mediators and the resident peritoneal cells involved in the neutrophil migration (NM) induced by mineral trioxide aggregate (MTA) in mice. Study design: MTA (25 mg/cavity) was injected into normal and pretreated peritoneal cavities (PC) with indomethacin (IND), dexamethasone (DEX), BWA4C, U75302, antimacrophage inflammatory protein-2 (MIP-2), and anti-interleukin-1β (IL-1β) antibodies and the NM was determined. The role of macrophage (MO) and mast cells (MAST) was determined by administration of thioglycollate 3% or 48/80 compound, respectively. The concentration of IL-1β and MIP-2 exudates was measured by ELISA. Results: MTA induced dose- and time-dependent NM into mice PC, with the participation of MO and MAST. NM was inhibited by DEX, BWA4C, and U75302, as well as anti-MIP-2 and anti-IL-1β antibodies. In the exudates, IL-1β and MIP-2 were detected. Conclusions: This study suggests that MTA induces NM via a mechanism dependent on MAST and MO mediated by IL-1β, MIP-2, and LTB4. © 2008 Mosby, Inc. All rights reserved.
Keywords: aluminum derivative; antiinflammatory agent; calcium derivative; CXCL2 chemokine; interleukin 1beta; leukotriene B4; mineral trioxide aggregate; oxide; root canal filling material; silicate; animal; Bagg albino mouse; cytology; drug combination; drug effect; macrophage; mast cell; mouse; neutrophil chemotaxis; peritoneal cavity; physiology; Aluminum Compounds; Animals; Anti-Inflammatory Agents; Calcium Compounds; Chemokine CXCL2; Drug Combinations; Interleukin-1beta; Leukotriene B4; Macrophages; Mast Cells; Mice; Mice, Inbred BALB C; Neutrophil Infiltration; Oxides; Peritoneal Cavity; Root Canal Filling Materials; Silicates